Riglyne vir voortgesette teologiese opleiding: Uitdagings vir die AGS-kerk - Andries Putter (Verbum et Ecclesia, 2010)
Guidelines for continuous theological training: Challenges for the Apostolic Faith Mission church Qualitative research done amongst a section of the broader membership as well as a region of the Apostolic Faith Mission (AFM) church has identified the role expectations of the pastor. Studies have shown that pastors should be continuously equipped to enable them to meet all their role expectations successfully. Although successful pastorates are a priority for the AFM, no formal structures have been constituted to guide pastors to become involved in continuous theological training. A literature research was also undertaken in order to obtain a larger and representative picture of the continuous training of pastors. The research and literature study findings have led to the drafting of proposed guidelines for continuous theological training. The purpose of this article is to provide these guidelines to the AFM church role players for them to remain informed regarding continuous theological training. This will enable pastors to stimulate congregational growth and address different training needs.